Clinical and epidemiological presentation of COVID-19 among children in conflict setting - Dar Iang, Maureen; Hassan, Ola El Hajj; McGowan, Maureen; Basaleem, Huda; Al-Sakkaf, Khaled; Jahn, Albrecht; Dureab, Fekri (Children, 2022)
Background: This study aims to describe the observable symptoms of children with COVID-19 infection and analyze access to real-time polymerase chain reaction (RT-PCR) testing among children seeking care in Yemen. Method: In the period of March 2020-February 2022, data were obtained from 495 children suspected to have been infected with COVID-19 (from a larger register of 5634 patients) from the Diseases Surveillance and Infection Control Department at the Ministry of Public Health and Population in Aden, Yemen. Results: Overall, 21.4% of the children with confirmed COVID-19 infection were asymptomatic. Fever (71.4%) and cough (67.1%) were the most frequently reported symptoms among children, and children were less likely to have fever (p < 0.001), sore throat (p < 0.001) and cough (p < 0.001) compared to adults. A lower frequency of COVID-19-associated symptoms was reported among children with positive RT-PCR tests compared to children with negative tests. A lower rate of testing was conducted among children (25%) compared to adults (61%). Fewer tests were carried out among children <5 years (11%) compared to other age groups (p < 0.001), for children from other nationalities (4%) compared to Yemeni children (p < 0.001) and for girls (21%) compared to boys (30%) (p < 0.031). Conclusion: Understanding and addressing the cause of these disparities and improving guidelines for COVID-19 screening among children will improve access to care and control of the COVID-19 pandemic.